Critical Thinking and Literacy in the Digital Era: A Literature Review on Essential Skills for 21st Century Learners - Ni Ketut Anggriani; Nanda Aulia Pratiwi; Dewa Dwi Pranahita; Paramita Putri Apriyani; Sintya Dewi Lestari (Indonesian Journal of Teacher Education, 2026)
The rapid development of digital technology has transformed the way individuals access, process, and utilize information in various aspects of life, including education. In the context of 21st-century learning, students are required to possess digital literacy and critical thinking skills to evaluate information effectively in an increasingly complex digital environment. This study aims to analyze the relationship between digital literacy and critical thinking as essential skills for 21st-century learners. This research employed a Systematic Literature Review (SLR) method by examining 30 scholarly articles published between 2016 and 2025. The data were collected from several academic databases, including Google Scholar, DOAJ, ERIC, and ScienceDirect, using the keywords critical thinking, digital literacy, digital learning, and 21st-century skills. The article selection process followed the PRISMA approach, while thematic analysis was used to identify research patterns and key themes. The results indicate that digital literacy plays a significant role in enabling students to access, understand, and critically evaluate digital information. Furthermore, the integration of digital technology in learning environments can enhance students’ critical thinking skills through activities such as information analysis, online discussions, and collaborative learning. The findings also reveal that digital literacy and critical thinking are closely interconnected and mutually reinforcing competencies that support effective learning in the 21st century. Therefore, integrating these competencies into educational curricula is essential to prepare students for the challenges of the digital era.